Nonalcoholic fatty liver disease developed after pancreatoduodenectomy for solid pseudopapillary neoplasm in a 10-year-old girl: a case report - Toshio Sawai; Shogo Zuo; Taichi Terai; Satoshi Nishiwada; Kenji Nakagawa; Minako Nagai; Takehiro Akahori; Hiromichi Kanehiro; Masayuki Sho (Surgical Case Reports, 2022)
Abstract Background Solid pseudopapillary neoplasms of the pancreas are rare. Moreover, pancreatoduodenectomy (PD) and postoperative care are not common in pediatric surgery. Herein, we report a case of PD and nonalcoholic fatty liver disease (NAFLD) after PD and present a literature review. Case presentation A 10-year-old girl with a suspected liver tumor was referred to our hospital. Echography, enhanced computed tomography and magnetic resonance imaging showed that the tumor coexisted with the solid and cystic parts of the pancreatic head. Since the patient was a young woman and the imaging findings were consistent with that of pancreatic solid pseudopapillary neoplasms (SPNs), we diagnosed her with pancreatic SPN. Thereafter, PD was performed, and she was discharged 10 days after the operation. Although her postoperative course was mostly uneventful, she experienced few episodes of abdominal pain and diarrhea before hospital discharge. These symptoms subsequently became more frequent and severe. The patient was urgently readmitted to the hospital for watery steatorrhea and lower abdominal colic pain. Her serum aspartate aminotransferase and alanine aminotransferase levels were elevated, and a fatty liver was detected on echography. The patient was diagnosed with steatorrhea, peristaltic pain, and NAFLD after PD. Pancrelipase (containing pancreatic digestive enzymes), antidiarrheal agents, and probiotics were started. Dosage increase of these drugs reduced the defecation frequency and abdominal pain and switched diarrhea to loose stools. However, more lipids in meals or more meals caused diarrhea and abdominal pain. Therefore, the doses of these drugs were further increased, and another antidiarrheal agent, loperamide hydrochloride, was added. Exocrine pancreatic enzymes supplementation and careful follow-up should prevent NAFLD progression after PD. At present, the patient has occasional abdominal pain, but has tangible soft stools once or twice a day. Although echography still shows a mottled fatty liver, her hepatic enzymes are only mildly elevated. Conclusions Pediatric PD is rare, and residual pancreatic function is usually sufficient, unlike in adult cases. However, we experienced a case of NAFLD after PD for a pediatric pancreatic SPN, in which pancreatic enzyme supplementation effectively improved this condition. Further attention must be paid to worsening of NAFLD that can develop nonalcoholic steatohepatitis.